Two new species of Brachycephalus (Anura : Brachycephalidae) from the Atlantic Forest in Parana State, Southern Brazil - Alves, ACR; Ribeiro, L. F.; Haddad, CFB; Dos Reis, S. F. (Herpetologists League, 2006)
Two new species of brachycephalid frogs are described from Pico Marumbi, municipality of Morretes, and Pico da Igreja, municipality of Guaratuba, Parana State, southern Brazil. The new species share the following attributes: body bufoniform; skin on top of the head, and central part of the back body smooth with no dermal co-ossification; outer metatarsal tubercle distinct; dermal roofing bones of skull unornamented; all paired cranial bones distinct and not fused; quadratojugals, and maxillary odontoids present. The new species from Pico Marumbi is characterized by male SVL = 11.6-12.5 and female SVL = 13.0-14.5 turn; and general color orange with dorsal reddish-brown irregular markings, lateral surfaces with small dark brown spots, and belly with brownish spots and small dots. The new species from Pico da Igreja is characterized by male SVL = 12.6-13.9 and female SVL = 14.6-15.3 mm; and general color orange, lateral surfaces with small dark brown spots, and belly with brownish coalescent spots and small dots. Comparisons with other brachycephalid species and osteological data are provided.
Keywords: Amphibia; Anura; Atlantic forest; brachycephalidae; Brachycephalus; new species; osteology; Southern Brazil